Prevalence and factors associated with body mass index in children aged 9-11 years - Gerson Luis de Moraes Ferrari; Victor Matsudo; Peter T. Katzmarzyk; Mauro Fisberg (Brazilian Society of Pediatrics, 2017)
Objective: This study aimed to identify the prevalence and factors associated with body mass index (BMI) in children aged 9-11 years. Methods: The study is part of the International Study of Childhood Obesity Lifestyle and the Environment (Iscole). Body composition was determined using the bipolar bioimpedance technique. The mean BMI value was categorized as recommended by the World Health Organization. For seven consecutive days, participants used an accelerometer to objectively monitor sedentary behavior (SB) and moderate to vigorous physical activity. Individual factors (anthropometric and behavioral), family aspects, and family and school environment were provided by participants and parents and were analyzed by multilevel linear regression adjusted for gender, ethnicity, school, number of siblings, and total annual family income. Results: The mean BMI was 20.1 kg/m2, and 51.8% of the children were overweight/obese (50.3% boys, 53.4% girls, p = 0.014). Considering all participants, the associated factors of BMI were body fat percentage (BF%, β = 0.0216, p < 0.001) and screen time (ST, β = 0.0050, p = 0.006). In boys, the associated factors were BF% (β = 0.0209, p < 0.001), ST (β = 0.006, p = 0.036), and healthy eating policies or practices (β = 0.0276, p = 0.025). In girls, only BF% was associated (β = 0.0221, p < 0.001) with BMI. Conclusions: High prevalence of overweight/obesity was observed in children from São Caetano do Sul. Different associated factors were identified between the genders, with only BF% being common in both genders.